The role of Tranexamic acid in the Reduction of Bleeding in Abdominal Aortic Aneurysm Surgery - Yaqub, Khan Muhammad; Saeed, Muhammad; Yasin, Bilal; Ameer, Khalid; Noor, Nusrat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the effects of Tranexamic acid on intraoperative blood loss.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Jun to Oct 2021.Methodology: A total of 96 patients from both genders undergoing elective open abdominal aortic aneurysm surgery under general anaesthesia enrolled in the study after random distribution to Drug and Control Groups. The primary determinant was intraoperative blood loss. Additionally, determining variables were intraoperative and postoperative blood transfusions, thromboembolic episodes, and postoperative mortality rate.Results: A total of 96 patients enrolled in the study, out of which 90(93%) were males, whereas 6(7%) were females, with a mean age of 65.37±7.01 (55–75 years). Of 96 participants, 52(54%) patients were from ASA Class II and 44(46%) were from ASA Class III. There was no significant correlation between surgical time (p-value 0.45), clamping time (p-value 0.34), and intraoperative and postoperative transfusions (p-value 0.56 and 0.28, respectively). However, a statistically significant reduction in intraoperative and postoperative blood loss was recorded (p-value